Effects of scaling and root planing and sub-antimicrobial dose doxycycline on oral and systemic biomarkers of disease in patients with both chronic periodontitis and coronary artery disease - Gu¨ lay Tu¨ ter (Blackwell Synergy, 2007)
Objectives: This study evaluated the effects of scaling and root planing (SRP) sub-antimicrobial dose doxycycline (SDD) on gingival crevicular fluid (GCF) levels of matrix metalloproteinase (MMP) -1, -8, -13 and on serum levels of high-sensitivity C-reactive protein (HsCRP) and lipid fractions in patients with both chronic periodontitis (CP) and coronary artery disease (CAD). Material and Methods: Thirty-six patients were randomly distributed into two groups (Placebo or SDD; 6 weeks) and both received two regimens of SRP. At baseline and 6 weeks, GCF and blood were collected and clinical indices were recorded. MMPs, HsCRP and lipid fractions were assayed. Results: There were statistically significant improvements for all clinical parameters, GCF volumes, GCF MMPs and serum levels of HsCRP, apolipoprotein-A (APO-A), high-density lipoprotein (HDL) and lipoprotein-a between pre- and post-treatment in both groups. Between groups, there were statistically significant greater improvements in pocket depth (PD), gingival index (GI), APO-A and HDL, favouring the group receiving SDD adjunctive to SRP (po0.05). Conclusion: Greater improvement was detected for PD and GI, and for serum levels of APO-A and HDL cholesterol when using SRP1SDD compared with SRP1placebo in this study. An investigation with larger numbers of patients and a longer duration of drug treatment is needed to confirm these preliminary findings.